Role of leukocyte parameters in patients with ST-segment elevation myocardial infarction undergoing primary percutaneous coronary intervention with high thrombus burden - Wang, Hao; Li, Shixing; Yu, Jin; Xu, Jingsong; Xu, Yan (Frontiers in Cardiovascular Medicine, 2024)
Objective Leukocyte parameters are associated with cardiovascular diseases. The aim of the present study was to investigate the role of leukocyte parameters in patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PPCI) with high thrombus burden (HTB). Methods A total of 102 consecutive STEMI patients with HTB who underwent PPCI within 12 h from the onset of symptoms between June 2020 and September 2021 were enrolled in this study. In addition, 101 age- and sex-matched STEMI patients with low thrombus burden (LTB) who underwent PPCI within 12 h from the onset of symptoms were enrolled as controls. Leukocyte parameters, such as neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and monocyte to lymphocyte ratio (MLR), were calculated at the time of admission. Results The value of NLR and MLR were significantly higher in the HTB group than in the LTB group (6.24 ± 4.87 vs. 4.65 ± 3.47, p = 0.008; 0.40 ± 0.27 vs. 0.33 ± 0.20, p = 0.038). A cutoff value of >5.38 for NLR had a sensitivity and specificity of 53.9% and 74.3%, respectively, and MLR >0.29 had a sensitivity and specificity of 60.8% and 55.4%, respectively, for determining the STEMI patients with HTB [area under the receiver operating characteristic curve (AUC): 0.603, 95% confidence interval (CI): 0.524–0.681, p = 0.012; AUC: 0.578, 95% CI: 0.499–0.656, p = 0.046]. There was no significant difference of all-cause mortality rate and major adverse cardiac events (MACEs) between the STEMI patients with HTB or with LTB (3.92% in HTB group vs. 2.97% in LTB group, p = 0.712; 10.78% in HTB group vs. 8.91% in LTB group, p = 0.215). Compared with the HTB patients in the low NLR group, C-reactive protein, baseline troponin I, baseline brain natriuretic peptide, and leukocyte parameters, such as white blood cell, neutrophil, lymphocyte, NLR, PLR, and MLR, were also significantly higher in the high NLR group in STEMI patients who underwent PPCI with HTB (18.94 ± 19.06 vs. 35.23 ± 52.83, p = 0.037; 10.99 ± 18.07 vs. 21.37 ± 19.64, p = 0.007; 199.39 ± 323.67 vs. 430.72 ± 683.59, p = 0.028; 11.55 ± 3.56 vs. 9.31 ± 2.54, p = 0.001; 9.77 ± 3.17 vs. 5.79 ± 1.97, p = 0.000; 1.16 ± 0.44 vs. 2.69 ± 1.23, p = 0.000; 9.37 ± 4.60 vs 1.31 ± 2.58, p = 0.000; 200.88 ± 89.90 vs. 97.47 ± 50.99, p = 0.000; 0.52 ± 0.29 vs. 0.26 ± 0.14, p = 0.000, respectively). MACEs and heart failure in the high NLR group were significantly higher than that in the low NLR group of STEMI patients who underwent PPCI with HTB (20.45% vs. 4.25%, p = 0.041; 10.91% vs. 2.13%, p = 0.038). Conclusion The value of NLR and MLR were higher in STEMI patients who underwent PPCI with HTB. In STEMI patients who underwent PPCI with HTB, a raised NLR could effectively predict the occurrence of MACEs and heart failure.